2004
DOI: 10.1002/jnr.20011
|View full text |Cite
|
Sign up to set email alerts
|

Noise trauma alters D‐[3H]aspartate release and AMPA binding in chinchilla cochlear nucleus

Abstract: Exposure of adults to loud noise can overstimulate the auditory system, damage the cochlea, and destroy cochlear nerve axons and their synaptic endings in the brain. Cochlear nerve loss probably results from the death of cochlear inner hair cells (IHC). Additional degeneration in the cochlear nucleus (CN) is hypothesized to stem from overstimulation of the system, which may produce excitotoxicity. This study tested these predictions by exposing one ear of anesthetized adult chinchillas to a loud noise, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 50 publications
7
40
0
Order By: Relevance
“…In particular, the intrinsic excitability of the pyramidal neurons in the deafferented region of A1 is shown to be enhanced (Kotak et al 2005). Moreover, the excitatory synapses targeted on the deafferented neurons are strengthened (Vale et al 2002;Muly et al 2004;Kotak et al 2005) while the inhibitory synapses are weakened (Suneja et al 1998a, b;Vale et al 2002;Kotak et al 2005). These synaptic regulations are consistent with homeostatic plasticity, previously observed in the hippocampus ) and the visual cortex (Desai et al 2002).…”
Section: Introductionsupporting
confidence: 70%
“…In particular, the intrinsic excitability of the pyramidal neurons in the deafferented region of A1 is shown to be enhanced (Kotak et al 2005). Moreover, the excitatory synapses targeted on the deafferented neurons are strengthened (Vale et al 2002;Muly et al 2004;Kotak et al 2005) while the inhibitory synapses are weakened (Suneja et al 1998a, b;Vale et al 2002;Kotak et al 2005). These synaptic regulations are consistent with homeostatic plasticity, previously observed in the hippocampus ) and the visual cortex (Desai et al 2002).…”
Section: Introductionsupporting
confidence: 70%
“…Finally, one cannot discount the possibility that homeostatic mechanisms, as described by Schaette and Kempter (2006), might have compensated for any acute loss of hyperactivity that DCN ablation might have caused. In line with this view, earlier works have shown that deafferentation of central auditory centers leads to long-term effects that are very different from those observed shortly after the deafferenting procedure Morest et al 1997;Muly et al 2004;Suneja et al 1998aSuneja et al , 1998b. Studies examining the time course of the effects of complete DCN ablation on IC or cortical activity or on tinnitus would be of great value in bringing clarity to these issues.…”
Section: Loss Of Ic Hyperactivity After Dcn Ablation: Could It Be An mentioning
confidence: 90%
“…More relevant to the present work are studies in which acoustic trauma was used. Following trauma, degeneration of axons and cells in the cochlear nucleus occurs (Bilak et al, 1997;Muly et al, 2002;Kim et al, 2004b;Muly et al, 2004). The initial loss includes both excitatory and inhibitory synapses, but there is a return of excitatory synapses and of glutamate release and uptake, without a corresponding increase in inhibitory synapses.…”
Section: Mechanisms Of the Tail Responsementioning
confidence: 99%
“…Although the lesions produced by acoustic trauma are in the cochlea, secondary effects in the central nervous system may be important in determining the perceptual consequences of trauma (reviewed by Syka, 2002). Central effects of cochlear damage or ablation include degeneration of axons and neurons (Born and Rubel, 1988;Morest et al, 1998;Redd et al, 2000;Muly et al, 2002), formation of new synaptic connections (Kim et al, 2004a;Muly et al, 2004), rewiring of central circuits (Nordeen et al, 1983;Rajan et al, 1993;Leake et al, 2000), and changes in synaptic strength to favor excitation over inhibition (Suneja et al, 1998a;Abbott et al, 1999;Milbrandt et al, 2000;Mossop et al, 2000;Oleskevich and Walmsley, 2002;Vale and Sanes, 2002;Kim et al, 2004a). Each of these could influence substantially the central representation of sound.…”
Section: Introductionmentioning
confidence: 99%